Characteristic gut microbiota and metabolic changes in patients with pulmonary tuberculosis. Issue 1 (18th February 2021) - Wang, Shuting; Yang, Liya; Hu, Haiyang; Lv, Longxian; Ji, Zhongkang; Zhao, Yanming; Zhang, Hua; Xu, Min; Fang, Rongfeng; Zheng, Lin; Ding, Cheng; Yang, Meifan; et al.
Summary: Intestinal flora provides an important contribution to the development of pulmonary tuberculosis (PTB). We performed a cross‐sectional study in 52 healthy controls (HCs) and 83 patients with untreated active PTB to assess the differences in their microbiomic and metabolic profiles in faeces via V3‐V4 16S rRNA gene sequencing and gas chromatography–mass spectrometry. Patients with PTB had considerable reductions in phylogenetic alpha diversity and the production of short‐chain fatty acids, dysbiosis of the intestinal flora and alterations in the faecal metabolomics composition compared with HCs. Significant alterations in faecal metabolites were associated with changes in the relative abundance of specific genera. Our study describes the imbalance of the gut microbiota and altered faecal metabolomics profiles in patients with PTB; the results indicate that the gut microbiota and faecal metabolomic profiles can be used as potential preventive and therapeutic targets for PTB. Abstract : The imbalance of the gut microbiota and altered faecal metabolomics profiles in patients with PTB;Mtb infection decreased the production of SCFAs in faeces.